2019
DOI: 10.3390/app9204333
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Carbon Dioxide Emissions amongst Alternative Slab Systems during the Construction Phase in a Building Project

Abstract: Global warming is now considered to be one of the greatest challenges worldwide. International environmental agreements have been developed in response to climate change since the 1970s. The construction industry is considered one of the main contributors to global warming. In order to mitigate global warming effects, the construction industry has been exploring various approaches to mitigate the impacts of carbon dioxide emissions over the entire life cycle of buildings. The application of different structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…At the same time, cement is a main component of carbon emission materials, and reducing cement consumption can reduce the carbon emission of buildings in essence. In the future, optimizing the whole architectural design system based on the application of new renewable materials and nano materials is a major research topic to reduce the carbon emission of the architectural system [25,32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, cement is a main component of carbon emission materials, and reducing cement consumption can reduce the carbon emission of buildings in essence. In the future, optimizing the whole architectural design system based on the application of new renewable materials and nano materials is a major research topic to reduce the carbon emission of the architectural system [25,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…As a comprehensive environmental impact assessment method, the LCA method is widely used to evaluate the effect of energy consumption reduction in the construction industry [23][24][25]. The specific assessment method involves evaluating the potential environmental impact by compiling an inventory of inputs and outputs related to the product system, and then the results of the inventory analysis and impact assessment are evaluated [26].…”
Section: Life Cycle Framework Of the Whole Construction Process Of Prmentioning
confidence: 99%
“…At the design phase, choices in structural systems can result in some economies (Zhang & Zheng, 2020). The concrete floor slab can also take a variety of forms with variable performance with regard to emissions (Paik & Na, 2019). These structural systems and the associated materials are closely related to the building forms themselves (Thanapol & Chavalparit, 2020;Limphitakphong et al, 2020), the uses of the buildings and by extension, to the arrangement of buildings.…”
Section: Literature On Carbon Emissions Associated With Local Urban Developmentmentioning
confidence: 99%
“…Although many studies have analyzed the pollutant emissions of road transportation, there has been little research on pollutant emissions from transporting building materials in the construction industry. While Paik and Na [ 4 ], for example, dealt with the estimation of carbon dioxide emissions from a construction project, the CO 2 emissions from transportation were far smaller than those of other phases, even though they were of significance for the building construction. Similarly, Sandanayake et al [ 38 ] conducted a process-based greenhouse gas emission quantification study that showed about 14% of greenhouse gas emissions to be caused by transportation in foundation construction projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The construction industry is regarded as one of the main contributors to environmental damage since it consumes a large volume of energy and emits various pollutants [ 1 , 2 , 3 ]. This industry accounts for about 40% of global energy consumption and approximately 35% of total greenhouse gas emissions [ 4 , 5 , 6 ]. In particular, the life cycle of a building spans over a period of more than 50 years, which is much longer than the lifespans of other products or services [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%